Edward Schillebeeckx and contemporary theology - Depoortere, Frederiek; Boeve, L. (Lieven); Erp, Stephan van, 1966- (London ; New York : T & T Clark, 2010)
What are contemporary theologys challenges? What are its fruitful approaches? Who are its promising contributors? The contributions to this collection of essays try to find answers to these questions by making references to the Dutch Dominican scholar Edward Schillebeeckx, using his theology as a starting point for an up-to-date investigation and discussion. The theological work of Edward Schillebeeckx marks the transition from a pre-modern to a modern approach to Christian faith, Church, and theology. Already more than two generations of theologians have been trained in dialogue with his thou
In Memoriam Edward Schillebeeckx, OP (1914-2009); Letter from Edward Schillebeeckx to the Participants in the Symposium 'Theology for the 21st Century: The Enduring Relevance of Edward Schillebeeckx for Contemporary Theology' (Leuven -- 3-6 December 2; Preface; List of Contributors; INTRODUCTION: The Enduring Significance and Relevance of Edward Schillebeeckx? Introducing the State of the Question in Medias Res; Part I: 'God Is New Each Moment': The Question of God in Modernity; Part II: 'Everything Is Politics But Politics Is Not Everything': The Social Role of Theology
Includes bibliographical references and index.
Description based on print version record.
Keywords: Schillebeeckx, Edward, -- 1914-2009.; Catholic Church -- Doctrines -- History; Religion; RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- Systematic; Electronic books